2017
DOI: 10.1186/s12891-016-1348-5
|View full text |Cite
|
Sign up to set email alerts
|

Metacarpal bone loss in patients with rheumatoid arthritis estimated by a new Digital X-ray Radiogrammetry method – initial results

Abstract: BackgroundThe Digital X-ray Radiogrammetry (DXR) method measures the cortical bone thickness in the shafts of the metacarpals and has demonstrated its relevance in the assessment of hand bone loss caused by rheumatoid arthritis (RA). The aim of this study was to validate a novel approach of the DXR method in comparison with the original version considering patients with RA.MethodThe study includes 49 patients with verified RA. The new version is an extension of the BoneXpert method commonly used in pediatrics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…Knowing these limitations may help plan clinical and research studies comparing males and females and screening for fracture risk. (43)(44)(45) Some limitations of this study are important to discuss. First, the cadaveric collection was limited to adult white male and female donors.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Knowing these limitations may help plan clinical and research studies comparing males and females and screening for fracture risk. (43)(44)(45) Some limitations of this study are important to discuss. First, the cadaveric collection was limited to adult white male and female donors.…”
Section: Discussionmentioning
confidence: 95%
“…Given that identifying individuals with poor bone health is critical for optimizing treatments and reducing fracture risk, ( 11 ) additional studies are warranted to determine if the morphology‐strength associations reported herein represent those of populations of clinical interest. ( 44 ) Finally, we focused exclusively on metacarpal morphology which can be measured from hand radiographs. However, whole‐bone strength also depends on tissue‐level mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, through MIAF, the software we used here for bone erosions analysis, it was possible quantifying precisely both bone erosions in cubic millimeters (mm 3 ) and periarticular bone loss [ 20 , 28 ], as well as focal BMD around erosions [ 14 ]. Digital x-ray radiogrammetry is another method frequently used in many studies to assess hand or MCP BMD in arthritis patients, showing a good correlation between local bone loss and disease progression, but this still represents a semiquantitative method [ 7 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…EineBestimmungderKnochenmineraldichteanhandvonRönt genaufnahmen im Bereich der Metakarpalknochen ist durch die DigitaleRadiogrammetrieetabliert [19,20].DieDigitaleRadio grammetrie basiert auf einer computerbasierten Analyse (Digital X-rayRadiogrammetry[DXR],z.B.Pronosco ® /SectraSystem bzw. Bone Xpert-System)vonHandröntgenaufnahmenmiteinerQuanti fizierungderKnochenmineraldichteimBereichderMetakarpalkno chenII-IV [21,22].DieDigitaleRadiogrammetrieistdurcheine hohe Reproduzierbarkeit der Messergebnisse (DXRBMD -Varia tionskoeffizient:0,13%-1,50%)gekennzeichnet [23].…”
Section: Digitale Radiogrammetrieunclassified